Enhancing Malaysia construction performance: application of lean technique in eliminating construction process waste. - Lim YenWui, I.; Abdul Rahman, H.; Abdul Samad, Z. (2009)
Poor project performance in Malaysian construction industry is not an uncommon scenario as the construction industry involves numerous parties, lengthy processes and different stages. The construction industry has unfortunate reputations in delivering projects that are unpredictable in terms of on time delivery, within budget and to the pre-specified quality, whilst concurrently attempting to ensure a zero accident rate. The Malaysian construction industry had carried out several mega projects in the past two decades but most of these projects were not cost, time and quality effective. There are a lot of non-value adding activities or wastes in construction processes and many among those were left unnoticed or unattended. Waste has been considered a major problem in the construction industry. Waste does not only have an impact on the efficiency of the construction industry but also on the overall state of the economy of the country. Previous studies have shown that tremendous productivity improvements can be achieved by simply targeting at reducing or eliminating those wastes and/or improve the process flow. Waste is defined as any losses produced by activities that generate direct or indirect costs, but do not add any value to the product from the point of view of the client. Accordingly, higher productivity could be achieved by minimizing wastes. In order to achieve that, there are dire needs for immediate changes in the industry. One of the major hindrances to waste minimization is the difficulty in establishing a proper methodology which can be used to benchmark future construction projects. Wastes that are mentioned earlier are identified by Taiichi Ohno as the seven wastes that are part of the Toyota Production System (TPS), which is also known as lean manufacturing or lean production. Lean manufacturing is a systemic approach to meeting customer expectations, whatever they value, by reducing waste. Lean production aims to optimize performance of the production system against a standard of perfection to meet unique customer requirements. Lean construction results from the application of this new form of production management to construction. Lean construction is much like the current practice, which has the goal of meeting the customer’s needs while using the least of everything. This study is part of an on-going research project aiming to enhance Malaysia construction productivity performance by eliminating non value-adding activities using lean construction techniques. This is meant to have a clearer picture on how “lean” is local construction performed pertaining to the concepts and principles of lean construction. In this paper, wastes in construction processes will be identified and potential application of value stream mapping tools to identify and eliminate construction process will be discussed.